1991
DOI: 10.1063/1.460381
|View full text |Cite
|
Sign up to set email alerts
|

Rotational diffusion of liquid toluene in confined geometry

Abstract: The effects of geometrical confinement on the molecular dynamics of liquid toluene in porous sol–gel silica glasses have been studied by the NMR method. The NMR deuteron spin–lattice relaxation times for toluene-d8, ortho-toluene-d1, and para-toluene-d1 were measured as a function of temperature for bulk and confined liquids. The rotational diffusion tensors for overall, internal, and anisotropic rotational diffusion have been determined. The effect of geometrical confinement results in a considerable decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 11 publications
1
31
0
Order By: Relevance
“…The most distinguishing feature of this study is that the 13 C relaxation of CS 2 in bulk or in pores are dominated by the spin-rotation interactions near room temperature, which is different from those in earlier studies [1][2][3][4][5][6][7][8] where quadrupolar or dipolar interactions play an important role in the nuclear relaxation.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…The most distinguishing feature of this study is that the 13 C relaxation of CS 2 in bulk or in pores are dominated by the spin-rotation interactions near room temperature, which is different from those in earlier studies [1][2][3][4][5][6][7][8] where quadrupolar or dipolar interactions play an important role in the nuclear relaxation.…”
Section: Introductionmentioning
confidence: 66%
“…Due to the particular sensitivity of NMR relaxation to the rotational and translational motions of molecules, it is not surprising to find that nuclear relaxation techniques have been successfully applied to investigate the effects of confined geometry on the dynamics of liquids. [1][2][3][4][5][6][7][8] The common NMR relaxation features for liquids in porous media include: ͑i͒ The spinlattice relaxation time T 1 is markedly decreased compared to the values in the bulk liquid; ͑ii͒ The spin-spin relaxation time T 2 is smaller than T 1 , even in the motionally narrowed regime (Ӷ1). The first theoretical model used to explain the relaxation behavior for confined liquid is the so-called two-state, fastexchange model.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, in a recent study of the rigid and planar glass-former, 1methylindole (1MID), with structure shown in the inset of Figure 1, a single secondary relaxation was resolved in the isothermal dielectric spectra, but its properties are at odds with those of the JG β-relaxations 29 of rigid molecules. For example, at T g , the separation of the β-loss peak from the α-loss peak of 1MID is more than 1 order of magnitude larger than toluene, a rigid and planar glass-former with a verified JG β-relaxation, 30,31 albeit the α-relaxation frequency dispersions of 1MID and toluene are almost the same. 32 More strikingly, when diluted by apolar molecules of larger and smaller sizes, the resolved βrelaxation time shows exactly the same temperature dependence as in pure 1MID.…”
mentioning
confidence: 96%
“…Earlier studies of toluene exhibit anisotropic motion in the liquid state. 30,31 For example, from nuclear magnetic resonance spin−lattice relaxation experiments, Hinze et al found that the β-relaxations in toluene show a pronounced anisotropy at temperatures below T g or at very high temperatures above 1.2T g . 31,42 Our results in Figure 4 show that the anisotropy in the β-relaxation of 1MID becomes more obvious at lower temperature (or higher pressure), where the energy barrier to overcome for relaxation is higher due to densification of the sample.…”
mentioning
confidence: 99%
“…A large part of the solvent is therefore expected to present a bulk-like behaviour. However, the interaction between the gelators and the solvent molecules leads to an organisation of the solvent close to the rigid parts, as well as a slowing down of its dynamics [23][24][25] . Such behaviour is commonly observed for liquids confined in matrices.…”
Section: If Structural Information On Lmmog Obtained By Transmission ...mentioning
confidence: 99%